PROGRAM PENDAMPINGAN, PELATIHAN AKUNTANSI SEDERHANA SECARA MANUAL DAN TERKOMPUTERISASI BAGI PT. GLOBAL BADJA WIJAYA - Irna Triannur Lubis; Oky Syahputra; Etty Harya Ningsi (Yayasan Nusantara Hasana Berdikari, 2025)
The ability to manage accurate financial records is an important aspect in supporting the sustainability and growth of a business, especially for companies that are developing. PT. Global Badja Wijaya as a local company engaged in the services and trade sector still faces challenges in implementing a structured accounting system, both manually and computerized. This community service activity aims to improve the company's HR capacity through a simple accounting mentoring and training program based on practice. The methods used include providing basic accounting materials, manual transaction recording simulations, and training in the use of simple accounting software. The results of the activity showed an increase in participants' understanding of the accounting cycle, the ability to prepare basic financial reports, and the use of spreadsheet applications and accounting software. In addition, this training also builds awareness of the importance of transparency and accountability in managing company finances. This activity is expected to be a foundation for the development of a better accounting information system in the future.